Catalogación y aprovechamiento de los pastos de montaña del Concejo de Somiedo - González Y.; Garcia-Manteca P.; Alvarez M.A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
In the Somiedo area (Asturias) was put into effect the pasture and meadows classification, in a study of territorial analysis. The agronomic value of pastoral resources to valuation the cattle potential in the area was estimated; integrating results of samplings with the other variables analysed (geology, vegetation, slope, altitude).
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)